Frailty and the psychosocial components of the edmonton frail scale are most associated with patient experience in older kidney transplant candidates – a secondary analysis within the kidney transplantation in older people (KTOP) study - Thind, Amarpreet K.; Levy, Shuli; Wellsted, David; Willicombe, Michelle; Brown, Edwina A. (Frontiers in Nephrology, 2023)
Background Older people with end-stage kidney disease (ESKD) are vulnerable to frailty, which impacts on clinical and experiential outcomes. With kidney transplantation in older people increasing, a better understanding of patient experiences is necessary for guiding decision making. The Kidney Transplantation in Older People (KTOP):impact of frailty on outcomes study aims to explore this. We present a secondary analysis of the Edmonton Frail Scale (EFS) and its relationship with patient experience scores. Methods The KTOP study is a single centre, prospective study, which began in October 2019. All ESKD patients aged ≥60 considered for transplantation at Imperial College Renal and Transplant Centre were eligible. Frailty was assessed using the EFS and 5 questionnaires assessed patient experience and quality of life (QoL) (Short Form-12(v2), Palliative Care Outcome Scale–Symptoms Renal, Depression Patient Health Questionnaire-9, Illness Intrusiveness Ratings Scale, Renal Treatment Satisfaction Questionnaire). The EFS was divided into 4 subdomains (psychosocial, physical function, medical status, and general health) and then compared with the questionnaire scores. Results 210 patients have been recruited (aged 60-78), 186 of whom completed EFS assessments. 118 (63.4%) participants were not frail, 36 (19.4%) vulnerable, and 32 (17.2%) were frail. Worse frailty scores were associated with poorer patient experience and QoL scores across all questionnaires. Severe deficits in the EFS psychosocial subdomain showed a statistically significant association with higher depression screen scores (coefficient 4.9, 95% CI 3.22 to 6.59), lower physical (coefficient -4.35, 95% CI -7.59 to -1.12) and mental function scores (coefficient -8.33, 95% CI -11.77 to -4.88) from the Short Form-12(v2), and lower renal treatment satisfaction scores (coefficient -5.54, 95% CI -10.70 to -0.37). Deficits in the physical function and medical status EFS subdomians showed some association with patient experience scores. Conclusion In the KTOP study cohort at recruitment vulnerable and frail candidates reported worse QoL and patient experiences. Severe deficits in the psychosocial subdomains of the EFS showed a strong association with patient experience and QoL, whilst physical function and medical status deficits showed a lesser association. This has highlighted specific EFS domains that may be suitable for targeted interventions to improve experiences and optimise outcomes.